The implications of bifurcated citizenship and access to land in Africa: the case of DRC conflict - Mbekezeli Comfort Mkhize; Chidochashe Nyere; Tuseku Dieudonné Tumba (Frontiers in Human Dynamics)
The history of colonialism has impacted negatively on violent conflicts in Africa. The DRC conflict remains one of the violent and protracted conflicts the world has ever come across. Although extensive research is well-documented regarding the conflict, concerted efforts to find a sustainable and lasting peace remain a huge conundrum. Access to land and bifurcated citizenship has had serious implications in the escalation of the conflict. This is largely because there is a fierce contestation between natives and non-natives in DRC. The non-natives originally migrated from Rwanda and fled to DRC due to 1994 genocide. Yet, despite these contestations, the scholarly works that focus exclusively on the implications of local dynamics including access to land and bifurcated citizenship remain miniscule. As a result, further scrutiny is required to examine the implications of access to land and bifurcated citizenship in DRC. Through critical examination of existing literature, this paper argues that failure to comprehend and respond to local dynamics has had adverse consequences on the DRC conflict. In response, this paper aims to dissect and demystify the implications of local dynamics on the escalation of conflict by employing social identity theory, relative deprivation theory and consociationalism theory. Employing these theoretical perspectives assists greatly in determining (1) the implications of ethnic and/or tribal diversity on the conflict and contestations for land; (2) the causes of the conflict, and (3) to suggest viable and context-specific responses that can provide an enabling environment for sustainable peace. The findings reveal that addressing the issue of access to land and bifurcated citizenship can go a long way in alleviating the conflict in DRC. The findings also reveal that finding an amicable solution in DRC depends on addressing local dynamics and finding a bottom-up/multi-level response. Consequently, this paper recommends an integrated and differentiated approach to dealing with the conflict in question.